Arsenical copper tools of Old Kingdom Giza craftsmen: First data. (April 2021) - Odler, Martin; Kmošek, Jiří; Fikrle, Marek; Erban Kochergina, Yulia V.
Highlights: Largest corpus from Egyptian Old Kingdom settlement analysed so far: 15 objects. Artefacts characterized also by metallography and micro-hardness. Arsenical copper and copper with impurities in the corpus confirmed, no tin bronzes. Full-size functional tools (chisel, two axe blades) were made of arsenical copper. Provenance of one artefact, needle 20966, tracked to Predynastic metalwork. Abstract: This study deals with the remains of metal objects from the settlement of workers living and labouring at the Egyptian site of Giza in the reigns of Dynasty 4 Kings Khufu and Khafra (c. 2500–2450 BCE). It provides the first detailed set of data on copper tools of the craftspersons working with wood, limestone, textile, etc., focusing on the major and trace element analyses, lead isotopes and microstructural description. Arsenical copper is again confirmed as a material practically used in the Old Kingdom, with arsenopyrite from Eastern Desert proposed as a source of arsenic. The CuAgAs needle 20966 has similar lead isotopes as two pieces of Predynastic Egyptian metalwork and litharge from late Uruk site Habuba Kabira (Syria), being probably a recycled specimen of earlier material connected to silver production. With 15 objects analysed in detail, it is for now the largest Old Kingdom corpus of metal objects from the settlement context.